Metaphors of Pedagogical Approaches in The Analects: A Descriptive Study of Their English Translations - Wu, Lin; Zhang, Xiaorong (Journal of Educational Research and Policies, 2026)
The Analects, widely regarded as a pinnacle of traditional Chinese intellectual heritage, embodies rich educational insights through abundant metaphorical expressions. Based on Conceptual Metaphor Theory, this study systematically investigates metaphors related to pedagogical approaches in the text. Using the English translations by Xu Yuanchong and James Legge as reference corpora, it analyzes corresponding translation strategies. The findings show that these translations effectively retain the metaphorical and philosophical essence of Confucian educational thought via targeted linguistic adaptation, thus promoting the cross-cultural communication of Confucian pedagogical ideas.